العناصر الزخرفية لواجهات المباني السكنية التقليدية بمدينة المكلا: د. صبري عوض التريمي ، د.فهد صالح جوهر - مجلة الأندلس للعلوم التطبيقية د. صبري عوض التريمي ، د.فهد صالح جوهر (مجلة الأندلس للعلوم التطبيقية, 2023)
الملخص EN Dealt with decorative elements in the Yemeni architecture، especially in Hadramout and cities، which require the collection and classification of these motifs and patterns and draw implications and design considerations. This paper aims to identify the elements of architectural and decorative traditional residential buildings in Mukalla to become our reference and background for future studies of the comprehensiveness of this subject. The research addresses the following points: provided and include (problematic - target - Methodology). The research also touched on the geographical location of the study area and the definition of the decoration and facades in addition to the classification of decorative elements in the facades of residential buildings in Mukalla and conclusions. Famous Yemenis since ancient art decorations architecture and tools، if we look carefully overall appearance of the groves of Yemen and engineering construction and components and architectural elements and decorative we inevitably find ourselves in front of the product of unique architecture reflects the creativity and originality and perfection and craftsmanship of Yemen in the planning، construction and methods of ornamentation and decoration، as well as high-capacity in the synthesizer between all these elements and to achieve harmony among them. Lies the importance of research as a documentary and analytical study of the decorative elements of the traditional residential buildings of the city of Mukalla، where he lacks the city to such studies، and is problematic Find the absence of rules and previous studies have.